Corrosion behavior of steel bar in chloride contaminated mortars with fly ash - Madlangbayan, Marish (Philippine Engineering Journal)
In this study, the corrosion behavior of steel in mortars with fly ash was investigated. Electrochemical measurements including the half cell potential, current density, anodic polarization and cathodic polarization were performed. The test results showed that corrosion current densities in chloride contaminated fly ash mortars with longer curing are within the passivity limit. Also, from the anodic polarization curves, the passivity grades in chloride contaminated fly ash mortars with longer curing were the same as Ordinary Portland Cement (OPC) mortars which indicates that mortars with this binder can provide passivity to steel bars as effective as OPC mortars. Moreover, by cathodic polarization test, fly ash mortars exhibited the ability to reduce oxygen availability which leads to enhancement in corrosion performance.